GERAK RANGKA TUBUH MANUSIA DALAM SENI LUKIS SURREALISME - SURYANTI, Drs. Idran Wakidi, Drs. Ismanadi Uska (Serupa The Journal of Art Education, 2013)
Background creation aims to lift something behind the contrasting view of aesthetic that has ben prevalent, in the form of surrealism painting are about the human object not from the standpoint of beauty beyond the ideal body shape alone, but about the motion of the human skeleton. Object inspired the human authors in their social environment so as to the process of creation begins with observation, appreciation, study field sketching, consult and then move the sketch has been approved on a white canvas with a brush and paints to embellish the work. Result of the completion of the final work instructions surrealism painting is up on stage ready to be exhibited and beneficial to society. Kata kunci: Gerak, Rangka manusia, surrealisme